(3GdZfjI (B( (3agQS TjhN GdbGVi YjGV (B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM CaFOJfG deYQaJg hHYO abO JYjf HMce GdMGce Ydi hCejd Ydi agGQS GdCTjGN Ydi GdYehe s
(3BNQgG (B:s
(3CHj GdMSf GdWjhQi hLejY QhGjGJg GdbGVi CHh Ydi hZjQg Yfg hGddg JYGdi faYfG HeG YdefGg EfJgJ GdagQSJ HMhd Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jHOG Hef GSeg eMeO hjfJgi HPcQ CHj GdMSf GdWjhQi HYV GdTQhM HNW fSN Hbde CMeO QGaY GdWgWGhi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs